Asian Indigenous Psychologies in the Global Context - Yeh, Kuang-Hui.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2019)
This volume introduces Asian indigenous psychologies with an emphasis on major theoretical and practical issues. The contributions demonstrate the potential for the indigenous psychologies of Asia to offer an alternative model of the internationalization of psychology-an internationalization not dominated by Western psychology. As a whole, this volume explores knowledge production outside of Western psychology; asks important questions about the discipline, profession, and practice of Asian indigenous psychology; makes critical appraises of cultural and psychological assumptions; sheds light on the dialectics of the universal and the particular in indigenous psychology; and explores the possibilities for a more equitable global psychology.
1. Introduction: Diversity among indigenous psychologies for complementarity but not for distinctiveness or competition -- 2. From Representing Culture to Fostering "Voice": Toward a Critical Indigenous Psychology -- 3. Cultures in Motion: Challenges to Future Inquiry -- 4. The Foundations and Goals of Psychology: Contrasting Ontological, Epistemological and Ethical Foundations in India and the West -- 5. The Story of Culture in Psychology and the Return Journey to Normology: Comments on the Global Relevance of Asian Indigenous Psychologies -- 6. Paternalistic Leadership: From Indigenous to Globalization -- 7. Indian Perspectives on the Synthesis of Spirituality and Materialism: Toward a Theory of Spiritual Creativity -- 8. Super-Ordinary Bias among Japanese: Is it unique to Japanese culture? -- 9. Indigenous implications and global applications of the dual filial piety model: Toward a psychological conceptualization of filial piety -- 10. How Does Trust Relate to Guanxi in the Chinese Workplace?: An Integrated Dynamic Model -- 11. Indigenous Psychology for the Others Chinese: Studying the Mind and Spirits among Ethnic Minorities in China -- 12. Self-Views of Aging, Filial Piety, Intergenerational Living Arrangement, and Well-Being in Taiwan -- 13. Asian Indigenous Psychology: Emerging Possibilities.
Keywords: Ethnopsychology; Psychology, Comparative; Psychology; Social sciences -- History; Ethnology -- Asia; Culture; Asia -- History; Cross-Cultural Psychology; Comparative Psychology; History of Psychology; Asian Culture; Asian History